Morphological and morphometric analysis of the sacral hiatus using lumbosacral spine CT scans: clinical relevance in caudal epidural analgesia - Apurba Patra; Harmeet Kaur; Priti Chaudhary; Adil Asghar; Navneh Samagh; Jerzy A. Walocha; Bartosz Rutowicz; Karolina Brzegowy-Solewska; Dariusz Lusina; Janusz Skrzat (Folia Morphologica)
BACKGROUND: To conduct a morphological and morphometric analysis of the sacral hiatus (SH) using lumbosacral spine CT scans and to evaluate its clinical relevance in caudal epidural analgesia (CEA). MATERIALS AND METHODS: This retrospective study analyzed 77 lumbosacral spine CT scans from a diverse patient population. The shape of the SH was classified into common types: inverted U, inverted V, irregular, and bilobed. Morphometric measurements included the length, width, and depth at the apex of the SH. The apex level of the SH was also determined in relation to the sacral vertebrae, and statistical analysis was performed to identify any correlation between the apex level and the morphometric dimensions. RESULTS: The most frequent SH shape was inverted U (68.83%), followed by inverted V (20.77%), irregular (9%), and a single instance of a bilobed shape (1.29%). The apex of the SH was most commonly located at the level of the S4 vertebra (75.32%), followed by the S3 vertebra (20.77%), S5 in two (2.59%), and S2 in one (1.29%). No significant correlation was found between the level of the apex and the length, width, or depth of the SH. These findings indicate a high degree of anatomical variability in the SH, independent of the apex level. CONCLUSIONS: The anatomical variability of the SH, as observed in this study, underscores the need for individualized assessment during CEA. The lack of correlation between the apex level and the morphometric dimensions of the SH highlights the importance of imaging modalities such as ultrasound or fluoroscopy to ensure precise localization and effective analgesia administration. These insights can improve clinical outcomes by enhancing the accuracy and safety of caudal epidural procedures.